A cytorhabdovirus-based expression vector in Nilaparvata lugens, Laodelphax striatellus, and Sogatella furcifera. (January 2022) - Xu, Wen-Ya; Fang, Xiao-Dong; Cao, Qing; Gao, Qiang; Gao, Dong-Min; Qiao, Ji-Hui; Zang, Ying; Xie, Liang; Ding, Zhi-Hang; Yang, Yi-Zhou; Wang, Ying; Wang, Xian-Bing
Abstract: The brown planthopper (BPH, Nilaparvata lugens ), the small brown planthopper (SBPH, Laodelphax striatellus ), and the white-backed planthopper (WBPH, Sogatella furcifera ) are problematic insect pests and cause severe yield losses through phloem sap-sucking and virus transmission. Barley yellow striate mosaic virus (BYSMV), a plant cytorhabdovirus, has been developed as versatile expression platforms in SBPHs and cereal plants. However, bio-safe overexpression vectors based on recombinant BYSMV (rBYSMV) remain to be developed and applied to the three kinds of planthoppers. Here, we found that rBYSMV was able to infect SBPHs, BPHs and WBPHs through microinjection with crude extracts from rBYSMV-infected barley leaves. To ensure bio-safety of the rBYSMV vectors, we generated an rBYSMV mutant by deleting the accessory protein P3, a putative viral movement protein. As expected, the resulting mutant abolished viral systemic infection in barley plants but had no effects on BYSMV infectivity in insect vectors. Subsequently, we used the modified rBYSMV vector to overexpress iron transport peptide (ITP) in the three kinds of planthoppers and revealed the potential functions of ITP. Overall, our results provide bio-safe overexpression platforms to facilitate functional genomics studies of planthoppers. Graphical abstract: Image 1 Highlights: BYSMV is able to infect Laodelphax striatellus, Nilaparvata lugens, and Sogatella furcifera by microinjection. A recombinant BYSMV mutant was developed into a bio-safe foreign protein expression platform in planthoppers. Overexpression of the iron transport peptide (ITP) resulted in light cuticle color and decreased insect survival in planthopper.